UMP trains entrepreneurs on herbal extraction and processing techniques - Ahmad Ziad, Sulaiman
The Faculty of Chemical & Natural Resources Engineering (FKKSA), MARA Entrepreneur Development Unit (PUSMA) and Centre of Continuing Education & Professional Development (CENFED) recently worked together to organise a workshop aimed at enhancing knowledge of its participants on local herbal extraction and processing techniques.